The 'Portuguese Range' as the Westernmost Maritime Region of Europe - Tiago Santos; Adriano Santos; Carlos Guedes Soares (European Regional Science Association (ERSA), 2015)
Ports located in the Portuguese west coast have been collectively defined as the ?Portuguese Range?, constituting a multi-port gateway system integrated within the broader context of an already well-established traditional maritime region. The aim of this paper is to identify how the Portuguese ports have been developing and how they can establish themselves as a gateway to the Iberian Peninsula and Western Europe. In fact, Portuguese range ports, located at the extreme of rail freight corridor n4, could greatly benefit from ?port regionalization? into bordering regions of Spain, the Madrid Community and Northern Europe, forming in this way a competitive gateway to foreland regions along the Atlantic Ocean, such as Latin America, North America, West Africa and Southern Africa. The paper first describes the current situation of Portuguese ports regarding infrastructure, superstructure and throughput, aiming at establishing its capabilities, level of activity and potential problems. Regional transport infrastructures current status, such as rail lines, inland terminals and dry ports are also reviewed, including projects currently foreseen by authorities. Main problems and bottlenecks in regional connections are identified. Main shipping lines calling in Portuguese ports, terminal operators, railway operators and 3P logistics service providers operating in Portugal are also identified. The strategies for promoting ?port regionalization? adopted by these different players in the supply chain are reviewed and analyzed, with focus on shipping lines, terminal operators, freight forwarders, port administrations and Governments. Conclusions are drawn and policy suggestions are made for further improvements in the regionalization of Portuguese ports, taken as an enhancer of economic growth.
Keywords: 330; Ports; Regionalization; Intermodalism; Logistics; Transport networks; Competitio